Navigating the redox landscape: reactive oxygen species in regulation of cell cycle - Mackova, Viktoria; Raudenska, Martina; Polanska, Hana Holcova; Jakubek, Milan; Masarik, Michal (Redox report, 2024)
Objectives: To advance our knowledge of disease mechanisms and therapeutic options, understanding cell cycle regulation is critical. Recent research has highlighted the importance of reactive oxygen species (ROS) in cell cycle regulation. Although excessive ROS levels can lead to age-related pathologies, ROS also play an essential role in normal cellular functions. Many cell cycle regulatory proteins are affected by their redox status, but the precise mechanisms and conditions under which ROS promote or inhibit cell proliferation are not fully understood.Methods: This review presents data from the scientific literature and publicly available databases on changes in redox state during the cell cycle and their effects on key regulatory proteins.Results: We identified redox-sensitive targets within the cell cycle machinery and analysed different effects of ROS (type, concentration, duration of exposure) on cell cycle phases. For example, moderate levels of ROS can promote cell proliferation by activating signalling pathways involved in cell cycle progression, whereas excessive ROS levels can induce DNA damage and trigger cell cycle arrest or cell death.Discussion: Our findings encourage future research focused on identifying redox-sensitive targets in the cell cycle machinery, potentially leading to new treatments for diseases with dysregulated cell proliferation.
Keywords: signální transdukce; Signal Transduction; reaktivní formy kyslíku; Humans; oxidative stress; redox-sensitive targets; Cell Cycle; proliferation; oxidace-redukce; lidé; zvířata; proliferace buněk; Reactive Oxygen Species; cell cycle signaling; Cell cycle; redox state; Cell Proliferation; reactive oxygen species; Oxidation-Reduction; poškození DNA; DNA Damage; Animals; buněčný cyklus